Chas referenduma . Chas referenduma . Referendum Hour . Час референдума - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the political situation, economic problems, and upcoming referendum in the Russian Federation. Featured in the program: Seliunin, Vasilii (People's Deputy); Latsis, Otto Rudol'fovich (Journalist); Zolotukhin, Boris (Politician); Nikonov, Viacheslav (Political Scientist); Shustov, Stanislav (People's Deputy); Dmitriev, Mikhail (Politician); Dmitriev, Viktor (Politician); Slavin, Boris (Publicist) Contributors: Dolgov, Georgii (Anchor) Обсуждение политической ситуации, экономических проблем и проведения референдума в России. В программе участвуют: Селюнин, Василий (Народный депутат); Лацис, Отто Рудольфович (Журналист); Золотухин, Борис (Политик); Никонов, Вячеслав (Политолог); Шустов, Станислав (Народный депутат); Дмитриев, Михаил (Политик); Дмитриев, Виктор (Политик); Славин, Борис (Публицист) Создатели: Долгов, Георгий (Ведущий/Ведущая)